Taxonomy and phylogeny of Lineus torquatus and allies (Nemertea, Lineidae) with descriptions of a new genus and a new cryptic species. Issue 1 (2nd January 2018) - Chernyshev, Alexei V.; Polyakova, Neonila E.; Turanov, Sergei V.; Kajihara, Hiroshi
Abstract : The heteronemertean genus Lineus Sowerby, 1806 has been badly in need of revision because of its apparent non-monophyly. In this paper, we focus on Lineus torquatus Coe, 1901, one of the heteronemertean species that occur commonly in waters around the North Pacific, as well as a few other allied species distributed in the western North Pacific, including Lineus alborostratus Takakura, 1898 and Cerebratulus montgomeryi Coe, 1901. Based on phylogenetic analyses using 16S, COI, 28S, 18S, and H3 gene and ITS sequences, we detected a well-supported clade comprised of heteronemerteans with a frontal white band on the head, to which we add Kulikovia gen. nov. This genus is nested within a more comprehensive, highly supported clade, here named the Siphonenteron -clade, which contains Tenuilineus bicolour (Verrill, 1892), Lineus flavescens Coe, 1905, Siphonenteron bilineatum (Renier, 1804), S. cf. bilineatum, Lineus cf. caputornatus, and Lineus sp. from Guam. Our analyses confirmed the presence of a cryptic species of what was formerly known as the cherry-red and reddish forms of Lineus torquatus, herein described as Kulikovia manchenkoi sp. nov. based on some external characters, internal morphology, and the four genetic markers ( COI, 16S, H3, and ITS ). In contrast to the species pair K. torquata – K. manchenkoi, the reddish form of K. alborostrata does not differ genetically from the typical form of this species. The significance of the external and internal characters for distinguishing cryptic species is discussed. http://zoobank.org/urn:lsid:zoobank.org:pub:9BECBC60-9C82-48EC-AD36-FC564D82A5BC http://zoobank.org/urn:lsid:zoobank.org:act:D02B2339-4F65-4517-9B13-DD4AAB0C55C5 http://zoobank.org/urn:lsid:zoobank.org:act:8D239B62-E655-4721-90F0-A4944DD8A3C7